Zgodovina opere in zgodovinska opera - Pompe, Gregor (Primerjalna književnost, 2007)
The main goal of this paper is to define the genre of historical opera, mainly in its relationship to literary- historical genres. It is clear that historical opera encompasses an essentially narrower field than the historical novel. As a criterion, the "historicity" of a theme does not prove to be sufficient because historical opera should display its characteristics on a formal musical level, as well as in its dramatic construction.
Keywords: literature; književnost; opera; zgodovinska opera; zgodovinski roman; libreto